Immunity and central nervous system (CNS) chronic acquired toxoplasmosis - Bodnya, K; Bobrova, O; Kotsyna, S; Vernigora, I (Annals of Mechnikov's Institute, 2020)
When chronic acquired toxoplasmosis (САT) the regularities of changes in the ratio of the immune system (CD3, IRI, total immunoglobulins) and the functional state of the central nervous system (EEG changes on stem-diencephalic type) available informative methods, which made it possible to evaluate the severity of the flow chart and predict treatment outcome without resorting to complex research methods. Found that the host-parasite relationships and clinical manifestations of chronic toxoplasmosis depend largely on protective and adaptive responses and compensatory abilities of the human body.